Soil carbon and phosphorus pools in field crop rotations in pampean soils of Argentina - Ciampitti, Ignacio A. (2011)
In temperate cropping systems, a better understanding of soil C and P transformations is pertinent to evaluate crop management consequences in the medium term. Six-year cropping systems experiments consisting of corn (Zea mays L.)-double-cropped wheat (Triticum aestivum L.)/soybean [Glycine max (L.) Merr.] (two sites) and corn-soybean-double-cropped wheat/soybean (two sites), with (Fp) or without P added (Wp), were evaluated in the Pampean soils of Argentina. The objectives were (i) to quantify the effects of continuous P fertilization on the size and vertical distribution of C and P in total organic C (TOC) and particulate organic matter (POM) fractions and (ii) to evaluate the POM-P fraction as a potential indicator of crop P availability. Annually, an average P rate of 34 kg P ha -1 was applied in Fp plots. The TOC, total P (TP), POM-C, and POM-P were measured in the 0- to 5-, 5- to 10-, and 10- to 20-cm soil depths at the end of the 6-yr period. Phosphorus fertilization increased TOC from 0.5 to 2.5 g C kg -1 and TP from 24.1 to 77.4 mg P kg -1 in the 0- to 20-cm depth. The POM-C and POM-P fractions were more sensitive than TOC or TP to P fertilization, increasing by 14 and 47%, respectively, in the 0- to 20-cm depth under continuous P addition. The greatest diff erences in POM-C and POM-P among treatments occurred in the surface soil layer. A signifi cant relationship was found between POM-P and corn P uptake at anthesis.